Microglia: Lifelong Patrolling Immune Cells of the Brain - Eyo, Ukpong B. (Prog Neurobiol, 2019)
Microglial cells are the predominant parenchymal immune cell of the brain. Recent evidence suggests that like peripheral immune cells, microglia patrol the brain in health and disease. Reviewing these data, we first examine the evidence that microglia invade the brain mesenchyme early in embryonic development, establish residence therein, proliferate and subsequently maintain their numbers throughout life. We, then, summarize established and novel evidence for microglial process surveillance in the healthy and injured brain. Finally, we discuss emerging evidence for microglial cell body dynamics that challenge existing assumptions of their sessile nature. We conclude that microglia are long-lived immune cells that patrol the brain through both cell body and process movements. This recognition has significant implications for neuroimmune interactions throughout the animal lifespan.